THE EFFECT OF UNDERSTANDING TAXATION, TAXPAYER AWARENESS, AND TAX SANCTIONS ON COMPLIANCE OF MSME TAXPAYERS IN CIREBON CITY - Sinsin Putri Yuliani; Tri Ayu Sistalia; Agung Yulianto (Cirebon International Conference on Education and Economics Proceeding, 2024)
Due to the fact that many MSME participants fail to pay taxes, tax income has decreased. The government has to educate the public on the value of paying taxes in order to promote tax compliance. Using taxation counseling in Indonesia to give socialization to the community in the form of guidance, comprehension, and methods is a successful first step. Therefore, the goal of this study is to evaluate and analyze the impact that tax penalties, taxpayer knowledge, and taxpayer comprehension of taxes have on taxpayer compliance in Cirebon City's micro, small, and medium-sized businesses (MSMEs). The study's findings suggest that comprehension of taxes influences taxpayer compliance, as does the impact of tax penalties and taxpayer awareness. This study can be used by the Directorate General of Taxes to promote a more robust tax policy and awareness, particularly among micro, small, and medium-sized businesses (MSMEs) in the city of Cirebon.